Comparison of gluteal muscle central activation in individuals with and without patellofemoral pain - Ho, Kai-Yu; Carpio, Michael; Donohue, John; Kissman, Jacob; Liang, Jing Nong (Frontiers in Physiology, 2025)
Patellofemoral pain (PFP) is often linked to knee valgus during weight-bearing activities, commonly attributed to gluteal muscle weakness. However, recent research suggests that central nervous system adaptations may also influence muscle function and movement patterns in individuals with PFP. This study compared the central activation ratio (CAR) of the gluteus medius and gluteus maximus between individuals with and without PFP, and assessed the associations between gluteal CAR, frontal plane projection angle of the trunk and lower extremity, and knee function. Twelve individuals without PFP and 10 individuals with PFP participated. We tested CAR of the gluteal muscles with a superimposed burst protocol during a maximum voluntary isometric contraction and evaluated frontal plane kinematics of the trunk and lower extremities during five single leg tasks. Participants with PFP also completed the Anterior Knee Pain Scale (AKPS). Independent t-tests compared CAR between groups, and Pearson correlation coefficients evaluated the associations between CAR, frontal plane kinematics, and AKPS. Individuals with PFP tended to have lower gluteus maximus CAR, though the difference was not statistically significant (PFP: 90.8% ± 7.0%, Control: 94.4% ± 3.0%; p = 0.067). CAR of both the gluteus maximus (R = 0.790, p = 0.003) and gluteus medius (R = 0.584, p = 0.038) were significantly correlated with AKPS scores, and gluteus maximus CAR was associated with trunk lean angle during single leg landing (R = 0.533, p = 0.006). Our data suggest that higher gluteal CAR is associated with better function in individuals with PFP. Lower gluteus maximus CAR contributes to ipsilateral trunk lean during single leg landing, potentially to reduce external hip moments and muscle demand.